2022
DOI: 10.1063/5.0078995
|View full text |Cite
|
Sign up to set email alerts
|

Spin–orbit torque in a single ferrimagnetic GdFeCo layer near the compensation temperature

Abstract: We report spin–orbit torque (SOT) based on spin-torque ferromagnetic resonance (ST FMR) in a single ferrimagnetic layer. Temperature-dependent anomalous Hall resistance ([Formula: see text]) shows a magnetic compensation temperature ([Formula: see text]) of about 205 K. Temperature-dependent ST FMR is performed to quantify SOT; the torque is exerted to the total moment, and the SOT sign diverges as the temperautre approaches [Formula: see text]. X-ray photoelectron spectroscopy revealed that SOT arises due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Therefore, it can be concluded that there is a Dzyaloshinskii–Moriya interaction in the system that stabilizes the monochiral Néel domain walls. This fact is consistent with previous studies. , …”
Section: Results and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, it can be concluded that there is a Dzyaloshinskii–Moriya interaction in the system that stabilizes the monochiral Néel domain walls. This fact is consistent with previous studies. , …”
Section: Results and Discussionsupporting
confidence: 94%
“…This fact is consistent with previous studies. 25,26 Figure 3b shows the dependence of the x-position of the left and right domain walls for these four cases, where x = 0 corresponds to the center of the structure. It can be seen that the positions of the walls on the left and right sides asymptotically approach certain coordinates where the compensation point is realized.…”
Section: Effect Of An In-plane Field On a Domain Wall Positionmentioning
confidence: 99%
“…Although a possible explanation for this phenomenon remains unknown, bulk SOT might have a relationship similar to the Tb‐Co ferrimagnetic system. [ 241 ] If not, a completely different magnetic anisotropy gives rise to this phenomenon, that is, negligibly small in‐plane magnetic anisotropy for the 111‐Mn 4 N and PMA for the 001‐Mn 4 N.…”
Section: Tailored Magnetic Propertiesmentioning
confidence: 99%
“…[73,184,185] In recent years, it has been demonstrated that self-induced SOT allows the magnetization switching of antiferromagnetic, [237,238] ferromagnetic, [239,240] and ferrimagnetic single layers. [241] Experimental results on the efficient magnetization switching of 30 nm thick Mn 4 N single layer have been achieved, when a writing current pulse (J w ) is applied along an eight-terminal Hall-bar pattern. [236] The magnetic domain structure was probed as a planar Hall resistance (R xy ) with a probing current (J p ).…”
Section: Crystal Orientation Dependencymentioning
confidence: 99%
“…Gd x Co 1Àx is selected for a few reasons: (i) specific compositions of GdCo have a roomtemperature magnetic compensation (or low total angular momentum), 19 (ii) ultrafast magnetization dynamics and domain wall velocities 41 km s À1 are observed 13,14,20,21 and (iii) effective fields from SOT being at least an order of magnitude greater than other RE-TM alloys like CoTb or CoFeGd. 12,[22][23][24] PMA in Gd x Co 1Àx is a necessity if it is to be considered for the storage layer in MRAM or a bias-free microwave circulator, and it is typically achieved through heterostructures of heavy-metal (Pt and Ta)/ferrimagnetic layers. 14,19 However, several reports have shown that due the large negative enthalpy of RE for oxide formation, Gd in Gd x Co 1Àx is prone to oxidation and consequently poor magnetic properties when capped with an oxide layer or a metal that tends to oxidize from high-temperature annealing.…”
Section: Introductionmentioning
confidence: 99%